How Does Culture Matter? The Xin (Heart-Mind)-based Social Competence of Chinese Executives - Wei, Hongguo; Bilimoria, Diana; Li, Shaobing (Management and organization review, 2017)
In this study we explore the emotional and cognitive dimensions of Chinese business leaders’ social competence. We argue for a culturally inclusive conceptualization of leader social competence and its internal structure, which takes into account Chinese indigenous features. Data were collected by critical incident interviews from 42 top executives of small- and medium-sized private enterprises in China. A total of 302 competency episodes were included in the current study. Grounded theory was used for data analysis. The following xin (heart-mind)-based social competencies were referenced in episodes of effective Chinese competency-relevant social interactions: guanxi building and maintenance, empathy, inspiration with wisdom, empowerment and developing others, resilience, and appreciation of problem solving. Each of these competencies includes an emotional and a cognitive element and embodies dynamic interplay between the emotional and cognitive dimensions of social competence. Xin-based social competencies impact effective interactions in relational contexts that implicate the individual self, the organizational self, and their interactions. The theoretical contributions and practical implications of the findings are discussed.